TRANSCENDING DUAL ECONOMIES: REFLECTIONS ON 'POPULAR ECONOMIES IN SOUTH AFRICA'. (5th February 2014) - Callebert, Ralph
ABSTRACT A recent special issue of Africa on 'Popular Economies in South Africa' drew attention to local economies and to the livelihoods that link these popular, informal economies and the lives of the poor to the formal and global economies. This approach offers a promising avenue for questioning academic and policy discourses about unemployment and poverty in South Africa that are curiously reminiscent of the dualist modernization theories of the 1950s and 1960s. Both the idea of a South African 'underclass', as discussed by Jeremy Seekings and Nicoli Nattrass, and the discourse of a first and a second economy, notably promoted by former President Thabo Mbeki, assume a fundamental divide in South Africa's economy based on socio-economic exclusion. These assumptions, however, fail to capture the many ways in which people cross these divides in making a living and have problematic policy implications. Highlighting these many and complex connections, as the recent special issue did, as well as historicizing the informal economy can help us to conceptualize the South African economy as a whole rather than as existing in two separate worlds.